Reaction of maize, sorghum and Johnsongrass to Peronosclerospora sorghi - Bigirwa, G.; Adipala, E.; Esele, J.; Cardwell, K. (Informa UK Limited, 2000)
Development of sorghum downy mildew, incited by Peronoscleospora sorghi (Weston and Uppal) C.G. Shaw, on maize, sorghum and Johnson grass was investigated at two locations in Uganda during three seasons (1994 and 1995). More sorghum downy mildew developed on the Johnson grass and sorghum than on the maize at all locations and in all seasons. No significant differences were observed in sporulation of P. soghi on the three hosts. Leaf shredding occurred on the three hosts but was the least on maize. Cross-inoculation with both conidia and oospores was achieved on the three hosts. Since the fungal population formed oospores and sporulated readily on the three hosts, which is typical of the sorghum strain, the disease in Uganda is attributed to the sorghum strain.